" Global media " coverage of the ZDF Iin intervention in governance in Zimbabwe : the case of Al Jazeera and BBC - Kurwa, Timothy (Midlands State University, 2020)
This study sought to identify and establish the frames employed by Al Jazeera and the BBC in the coverage of the ZDF intervention in governance in Zimbabwe. The researcher was interested in unpacking all the meanings intended in the coverage of the ZDF intervention in governance. Framing theory informed the study The study employed archival research, textual analysis augmented with critical discourse analysis and prescriptive thematic analysis for data presentation. The study found out that the global media coverage of the ZDF intervention perpetuated the use of the negative frames on Africa such as political instability and conflict, war and coup. Discourses of human rights, democracy and governance were used to vindicate the intervention. Al Jazeera and the BBC portrayed the coup as an intervention aimed at removing a dictator from power. The study concluded that the global media warmed up to the ZDF intervention in governance in Zimbabwe that was anti-Mugabe thus the military intervention was a necessary evil.